Photosynthetic Effect in Selenastrum capricornutum Progeny after Carbon-Ion Irradiation - Wang, Jie (PLoS One, 2016)
A large proportion of mutants with altered pigment features have been obtained via exposure to heavy-ion beams, a technique that is efficient for trait improvement in the breeding of plants and algae. However, little is known about the underlying mechanisms by which the photosynthetic pigments are altered by heavy-ion irradiation. In our study, the photosynthetic characteristics of progenies from carbon-ion irradiated Selenastrum capricornutum were investigated. Five progenies deficient in chlorophyll a were isolated after carbon-ion exposure. Photosynthetic characteristics, photoprotection capacity and gene expression of the light-harvesting complex in these progenies were further characterized by the measurement of chlorophyll fluorescence parameters (Fv/Fm, ФPSII, NPQ, ETR), the de-epoxidation state of the xanthophyll cycle, the amount of lutein and quantitative real-time PCR. High maximum quantum yield of photosystem II at day 10 and high thermal dissipation ability were observed in progenies #23 and #37 under normal culture condition. Progenies #18, #19 and #20 showed stronger resistance against high levels of light steps than the control group (612–1077 μmol photons m (-2) s (-1), p< 0.05). The progenies #20 and #23 exhibited strong photoprotection by thermal dissipation and quenching of (3)Chl* after 24 h of high light treatment. The mRNA levels of Lhcb5, Lhcbm5 and Lhcbm1 of the light-harvesting complex revealed markedly differential expression in the five progenies irradiated by carbon-ion beams. This work indicates that photosynthetic efficiency, photoprotection ability and the expression of light-harvesting antennae in unicellular green algae can be markedly influenced by irradiation. To our knowledge, this is the first report on changes in the photosynthetic pigments of green algae after treatment with carbon-ion beams.